Evaluating the population‐level effects of oxycodone restrictions on prescription opioid utilization in Ontario. Issue 7 (6th May 2022) - Rudoler, David; Kurdyak, Paul; Gomes, Tara; Huang, Anjie; Jones, Wayne; Littleford, Stephanie; Paracha, Nabiha; Fischer, Benedikt
Abstract: Purpose: To investigate the impact of restrictions on access to long acting oxycodone on prescription opioid use and opioid‐related harms. Methods: Administrative health data from Ontario, Canada was used to measure differences in opioids dispensed and emergency department (ED) visits for opioid‐related overdose, poisoning, or substance use following provincial restrictions on access to publicly insured OxyContin (February 29, 2012) and OxyNeo (February 28, 2013). This study focused on the cohort of provincial drug insurance eligible people (people 65+ and select low‐income populations) who were dispensed oxycodone prior to the restrictions. Difference‐in‐differences models with a propensity score matched comparison group of people who were dispensed non‐oxycodone opioids were used to estimate the main effects. Results: In 6 months following the delisting of OxyContin, milligrams of morphine equivalents (MMEs) per person per week for all opioids fell by an average of 7.5% in people dispensed oxycodone relative to the comparison group, and an average of 13.8% in chronic recipients of oxycodone. In the 6 months following the restrictions on OxyNeo, MMEs per person per week fell by an average of 3.1% in all people dispensed oxycodone, and 25.2% in chronic oxycodone recipients. The decline in oxycodone dispensing among chronic oxycodone recipients corresponded with an increase in dispensing of other opioid formulations, particularly hydromorphone and fentanyl. No important differences were observed for ED visits related to opioid poisoning, overdose, or substance use disorder. Conclusions: Province‐wide restrictions on access to long acting oxycodone had an impact on quantities of all opioids dispensed to chronic recipients of oxycodone, but small impacts on the full population of people dispensed oxycodone; the decline in use was partially offset by increases in use of other publicly‐funded opioid formulations. This study suggests that policies limiting access to specific prescription opioids led to overall reductions in publicly funded prescription opioid use, particularly in chronic oxycodone recipients, without immediate evidence of changes in opioid‐related ED visits.